Patterns of Inhalant Use among Incarcerated Youth - Howard, Matthew O. (PLOS ONE, 2015)
Inhalant use is especially prevalent among antisocial youth and can have serious health consequences. However, the extant literature has not investigated how use of various inhalants may co-occur among incarcerated youth. This study begins to address this gap in the literature by using latent class analyses to form distinct typologies of inhalant use. Study participants were residents (N = 723) of 27 Missouri Division of Youth Services facilities. Interviews assessed psychiatric symptoms, antisocial traits, delinquency, trauma, suicidality, and substance use behaviors. The mean age of the mostly male, ethnically diverse sample was 15.5 (S.D. = 1.2) years old. The study revealed the following classes of inhalant use: (1) severe polyinhalant use; (2) moderate polyinhalant use; (3) gas and permanent marker use; and (4) low-use. Compared to the low-use class, members of the severe polyinhalant use class had experienced more than double the rate of head injuries, the highest rates of traumatic experiences, and the highest rates of mental illness diagnoses. The gas and markers class had the highest rate of reporting hearing voices, followed by the severe polyinhalant use class, and the moderate polyinhalant use class. Results of this study underscore the need to address the high rate of head injuries and mental health diagnoses that contribute to severe polyinhalant use